Allergic asthma manifestations in human and seropositivity to Toxocara, a soil-transmitted helminth of carnivores: A case-control study and scoping review of the literature - Bazargan, Nasrin; Lari, Azadeh Nasri; Borhani, Mehdi; Fasihi Harandi, Majid (Frontiers in Medicine, 2022)
Asthma is a common respiratory disease affecting humans. Helminth parasites, including Toxocara species, have been implicated as predisposing factors of asthma. However, various studies present different findings on asthma-Toxocara association. Herein, we investigated the association of asthma manifestations with Toxocara seropositivity in a case-control setting on 248 participants (147 women and 101 men), with 124 healthy individuals as the control group and 124 patients known to have asthma based on the medical records of asthma clinics of Kerman University of Medical Sciences. Consequently, we presented a scoping review of all previous studies carried out on this topic, summarizing current findings and existing knowledge on this issue. Of 248 participants, 31 (12.5%) were Toxocara-seropositive, of which 19 (15.3%) were in the patient group and 12 (9.7%) in the control group. A significant relationship was found between asthma severity and age in Toxocara-seropositive individuals (P < 0.04). We found no significant relationship between asthma and Toxocara seropositivity. We identified 7,724 related records in three major scientific databases, NCBI PubMed, Scopus, and Google Scholar. The review of the literature showed that there are 80 published articles on asthma-Toxocara relationship with contradictory findings. More than half of the studies were performed in only four countries, namely, Brazil, the Netherlands, the United States, and Iran. The study population in 70% of the studies were children, and few studies investigated asthma-Toxocara association in adults. The most common study designs for investigating the association of asthma and Toxocara seropositivity were cross-sectional (35.0%), case-control (27.5%), and animal experimental (12.5%) studies. This study found no significant relationship between asthma manifestations and toxocariasis in a case-control setting. However, a scoping review of the current literature suggests that further experimental and field longitudinal cohort studies are required to elucidate the nature of asthma-Toxocara interaction in humans.